Computer-based Learning Model in Early Schools During the Covid-19 Pandemic in Rural Areas - Kmurawak, Remuz MB; Setyaningsih, Diana; Tokoro, Yokelin; Inggaber, Mamberuman; Sampebua, Mingsep Rante (Universitas Negeri Padang, 2024)
The COVID-19 pandemic has affected many aspects of life. In education, the conventional learning process has drastically changed to online. Schools with good resources and infrastructure, of course, can quickly adapt. However, schools with limited infrastructure, as well as low teacher skills, are a challenge. This research is to study the implementation of e-learning in online kindergarten classes from the existing conditions, challenges, and learning strategies that will be applied in PAUD schools in Jayapura City. The results of this study can be used as a reference in making decisions for implementing more effective online learning at the PAUD level. To gather data, a survey was conducted among 20 kindergarten and early childhood teaching staff in Jayapura City using a combination of methods, including contacting the schools, WhatsApp, and Google Forms. The findings reveal that the kindergarten-level teaching staff are predominantly women, aged between 24 and 54 years, with the majority falling within the age range of 35-53 years. The study also highlights the importance of e-learning in the current pandemic, as it enables teachers to document the educational process, remain organized, and provide more effective support to students amid distance restrictions and other challenges. The study results show that e-learning is essential to be prepared, especially during a pandemic. The willingness to engage in e-learning can help teachers document the educational process, be more organized, and be more helpful to students amid distance restrictions and other effects. However, teachers still need training to improve skills related to digital literacy. The training is more on multimedia to support learning and create exciting learning content with Multimedia.